Caracterização e engenharia de defeitos em Zn82Se enriquecido usado como componente primordial do detector bolômetro - cintilador (DBC) - Bruno Cordeiro Silva (2021)
The semiconductor zinc selenide (ZnSe) enriched with the 82Se isotope is one of the most promising materials for the construction of a scintillating bolometer detector (DBC) detector for the study of the neutrinoless double beta decay (0νββ). This event is considered to be ultra-rare (≈ T1/2 = 10^25 years) and predicted in extensions of the Standard Model. Due to the rarity of the event and the high costs involved in the development of this detector, it is essential to optimize the physical properties of the material through manipulation of point defects, which we call defect engineering. In this work, ZnSe enriched with approximately 95% of the 82Se isotope, Zn82Se, was characterized mainly by electronic paramagnetic resonance (EPR), photo - EPR and photoluminescence (PL). We show that the standard Zn82Se grown by the Bridgman - Stockbarger technique presents two photoluminescence bands centered at 540 and 630 nm, associated with Cu2+ and A – centers, respectively. The A – center was identified through photo - EPR as a pair consisting of a zinc vacancy (deep acceptor) and an Al in a Zn site (shallow donor). The standard Zn82Se material shows good scintillation properties with quenching factor (QF ≈ 4), which allows distinguishing particles (α, β, γ) in DBC. Both properties are lost with post growth heat treatments of Zn82Se. In order to improve luminescent properties by increasing the concentration of A – centers we used fast neutrons and heat treatments to induce isolated zinc vacancies (VZn) and associate them with shallow donors forming donor-acceptor pairs with efficient radiative recombination. Our study shows that neutron irradiation induces, in addition to zinc vacancies, a new donor center called NC1, which we attribute to a zinc di-interstitial, both annihilated by heat treatment at about 100°C.